Understanding Global Trade & Human Rights - E. Tammy Kim (My University, 2016)
Document is intended to help people interested in reconciling the gap between human rights and trade at a global scale. It's intended audience is for a seminar participants of the 2005 WTO Ministerial Conference in Hong Kong.